2012
DOI: 10.5101/nbe.v4i2.p99-106
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Biological Synthesis Of Silver and Copper Nanoparticles

Abstract: The antimicrobial properties of silver nanoparticles were known since ancient times and silver ions are widely used as bactericidal agent. Researchers have also recommended the use of silver and copper ions as superior disinfectants for wastewater generated from hospitals containing infectious microorganisms. A wide range of nanophasic and nanostructured particles are being fabricated globally with the aim of developing clean, nontoxic and eco-friendly technologies. Use of ambient biological resources in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…The reduction of silver ions and the formation of stable nanoparticles occurred on 4 th day to synthesize silver nanoparticles. The interaction between nanoparticles and biomolecules have been studied through several analysis and found that, various terpenoids or alkaloids present in the plant extracts caused the bioreduction of metal ions and stabilization of AgNPs [13]. The plant assisted reduction due to phytochemicals are considered to be the main mechanism for the synthesis of nanoparticles.…”
Section: Uv-vis Spectral Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of silver ions and the formation of stable nanoparticles occurred on 4 th day to synthesize silver nanoparticles. The interaction between nanoparticles and biomolecules have been studied through several analysis and found that, various terpenoids or alkaloids present in the plant extracts caused the bioreduction of metal ions and stabilization of AgNPs [13]. The plant assisted reduction due to phytochemicals are considered to be the main mechanism for the synthesis of nanoparticles.…”
Section: Uv-vis Spectral Studiesmentioning
confidence: 99%
“…Biosynthesis of silver nanoparticles has advantages like slower kinetics, better manipulation and control over crystal growth and excellent stability [13]. But, microbial mediated synthesis of AgNPs is not industrially achievable as they need high maintenance of aseptic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, green methods have attained tremendous attention in synthesis of pure or oxide MNPs [24][25][26][27]. However, not real green nature of these methods is a major problem [28]. Generally, plant and bacteria are two important sources for green synthesis of NPs [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been considerable interest in developing methods for the biosynthesis of copper NPs as an alternative to physical and chemical methods. A literature review [11] revealed only few studies on the biosynthesis of copper NPs using fungi and none of the studies has used the yeast Rhodotorula mucilaginosa (R. mucilaginosa). On the other hand, several studies have investigated the biosynthesis of copper NPs using bacteria, for example, Hasan et al [12], Ramanathan et al [13], Singh et al [14] among others.…”
Section: Introductionmentioning
confidence: 99%